Legal Reform on Indonesia’s Carbon Trading Regulation: Implementation and Harmonization of International Law - Siciliya Mardian Yoel; F.X. Joko Priyono; F.X. Adji Samekto; Erlis Nurbani (Faculty of Law, Universitas Negeri Semarang, Indonesia, 2025)
Carbon trading is a system where companies can buy and sell carbon credits, with each credit allowing the emission of a specific amount of greenhouse gases. The Indonesian government has introduced new regulations to support carbon trading, but these need to fit seamlessly with existing international regulations due to Indonesia’s active participation in the carbon trading agreement. This research has two goals: first, to examine how comprehensive Indonesia’s carbon trading regulations align with international frameworks such as the Paris Agreement and the Kyoto Protocol. And second, to identify and assess challenges and opportunities in harmonizing Indonesian laws with these global standards. This research uses normative legal research by assessing primary, secondary, and tertiary legal materials, such as international agreements, Indonesia’s laws, previously published works in the areas, and other legal documents. This method is combined with case studies from different countries. This approach will help identify successful strategies and pitfalls in carbon trading, offering valuable insights into what works and what does not. The expected outcome is a comprehensive understanding of how Indonesia’s carbon trading regulations align with international standards. It will also assess the efficacy of the current system works and suggest improvements to enhance its effectiveness. Indonesia’s approach to incorporating international treaties into national law is not entirely clear-cut, exhibiting elements of both monism and dualism. However, there is a tendency towards dualism, where international treaties must be transformed into national regulations to be effectively applied and used as a legal basis in judicial decisions. While carbon trading is a key mechanism in international climate agreements, it faces significant criticisms and challenges, particularly regarding environmental justice.